The need for SMR in Lesotho and role of SMRs with various functions and features in achieving SDGs - Mojalefa Sello (Energy Strategy Reviews, 2024)
The current study reviews past studies on energy history and structure in Lesotho, the need for Small Modular Reactors (SMRs) and detailed highlights on advances, functions and role of SMRs towards Sustainable Development Goals (SDGs) are reviewed. The Study reveals that Lesotho is experiencing major energy challenges of about 155 MW peak energy demand which is predicted to reach about 211 MW by 2030 if the national electrification rises to 54% as it is currently at around 41%. The study further reveals that SMR designs could actually counter solve Lesotho's energy, agricultural and health challenges through their multi-functional abilities if the government invests in this nuclear technology of at least 200–300 MW. This could increase rural electrification which is currently at 10%, improve Agricultural production and eradicate poverty, and health sector through production and utilization of radioisotopes in these key sectors.